Estrategias que dinamicen la economía de las empresas del sector solidario Cúcuta Norte de Santander - Jessica Ferley Domínguez Rangel; Blanca Mayerly Beltrán- de la Ossa; Maryury Paola Ortega-Andrade (Mundo Fesc)
The reopening of the border between Colombia and Venezuela has had a significant impact on the cooperative economy of San José de Cúcuta in the department of Norte de Santander, creating a critical situation in the border state since its closure in August 2015. This study seeks to propose strategies to foster the development of solidarity sector organizations in this region in the face of these changing circumstances. The research employed a descriptive methodology with a qualitative approach, gathering relevant information from various documentary sources and conducting surveys of solidarity sector organizations registered with Supersolidaria. Three organizations were selected from each category—employee funds, cooperatives, foundations, and associations—to ensure adequate representation. The results of the data analysis offer a detailed understanding of the current situation of solidarity economy organizations following the border reopening, identifying significant trends in their economic and social dynamics. The types of organizations in the border area were fully characterized, providing insight into how they address the challenges and opportunities that have arisen. Based on the results, specific strategies were developed to foster the growth and development of each type of organization in the new economic and commercial context. These strategies are crucial for promoting sustainable economic development in San José de Cúcuta in the face of the challenges and opportunities posed by changes at the border, contributing significantly to strengthening the solidarity economy and improving the entrepreneurial capacity of local organizations.